Contrast-enhanced magnetic resonance imaging for the detection of ruptured coronary plaques in patients with acute myocardial infarction - Jansen, Christian H. P.; Perera, Divaka; Wiethoff, Andrea J.; Phinikaridou, Alkystis; Razavi, Reza M.; Rinaldi, Aldo; Marber, Mike S.; Greil, Gerald F.; Nagel, Eike; Maintz, David; Redwood, Simon; Botnar, Rene M.; et al. (PLoS ONE, 2017)
Purpose: X-ray coronary angiography (XCA) is the current gold standard for the assessment of lumen encroaching coronary stenosis but XCA does not allow for early detection of rupture-prone vulnerable plaques, which are thought to be the precursor lesions of most acute myocardial infarctions (AMI) and sudden death. The aim of this study was to investigate the potential of delayed contrast-enhanced magnetic resonance coronary vessel wall imaging (CE-MRCVI) for the detection of culprit lesions in the coronary arteries. Methods: 16 patients (13 male, age 61.9±8.6 years) presenting with sub-acute MI underwent CE-MRCVI within 24-72h prior to invasive XCA. CE-MRCVI was performed using a T1-weighted 3D gradient echo inversion recovery sequence (3D IR TFE) 40±4 minutes following the administration of 0.2 mmol/kg gadolinium-diethylenetriamine-pentaacetic acid (DTPA) on a 3T MRI scanner equipped with a 32-channel cardiac coil. Results: 14 patients were found to have culprit lesions (7x LAD, 1xLCX, 6xRCA) as identified by XCA. Quantitative CE-MRCVI correctly identified the culprit lesion location with a sensitivity of 79% and excluded culprit lesion formation with a specificity of 99%. The contrast to noise ratio (CNR) of culprit lesions (9.7±4.1) significantly exceeded CNR values of segments without culprit lesions (2.9±1.9, p<0.001). Conclusion: CE-MRCVI allows the selective visualization of culprit lesions in patients immediately after myocardial infarction (MI). The pronounced contrast uptake in ruptured plaques may represent a surrogate biomarker of plaque activity and/or vulnerability.
CRIS-Team Scopus Importer:2023-03-08